INDONESIAN NATIONAL IDENTITY - Sagala, Tiur Dame R (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
The concept of national identity in the midst of the development of globalization requires a country to strengthen its national identity in order to maintain the integrity and unity of the nation. This paper attempts to provide a contemporary view of the perception of national identity in a country. This paper focuses on the state of Indonesia. This paper uses discourse discourse studies and data collection uses literature studies